Long-term energy storage phase change material and preparation method thereof

By combining polyol with polyacrylic acid and calcium carbonate hydrogels to form a hydrogen bond network structure, the problem of spontaneous crystallization of phase change materials during cooling is solved, long-term storage and controllable release of thermal energy are achieved, and the advantages of low cost and simplified process are provided.

CN119505282APending Publication Date: 2025-02-25SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411402562.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing phase change materials spontaneously crystallize during cooling, making it difficult to achieve long-term storage and on-demand release of thermal energy.

Method used

By combining the polyol with polyacrylic acid and calcium carbonate hydrogel, a hydrogen bond network structure is formed, the supercooling state of the polyol is stabilized, crystallization is avoided, and long-term storage and controlled release of heat are achieved.

Benefits of technology

The long-term energy storage characteristics of maintaining non-crystallization for 2 months at room temperature are achieved, and the controlled release of heat is achieved through reheating and other forms, reducing production costs and simplifying the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505282A_ABST
    Figure CN119505282A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of phase change energy storage materials, in particular to a long-term energy storage phase change material and a preparation method thereof. The preparation method of the long-term energy storage phase change material provided by the invention comprises the following steps: adding polyol into a sodium carbonate solution, stirring and dissolving to obtain a first mixed solution; adding water into calcium chloride and polyacrylic acid, and mixing to obtain a second mixed solution; slowly adding the second mixed solution into the first mixed solution, violently stirring and cleaning to obtain the polyol hydrogel composite phase change material. The polyhydric alcohol hydrogel composite phase change material which can be stored for a long time and has good shape stability and heat storage performance is prepared by utilizing the method provided by the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of phase change energy storage materials, and in particular to a long-term energy storage phase change material and a preparation method thereof. Background Art

[0002] Phase change material (PCM) is an advanced thermal energy storage and management material with high thermal energy storage density and relatively constant phase change temperature range. In recent years, latent heat storage based on PCM has been considered as a very attractive thermal energy storage (TES) technology. It is widely used in thermal management fields such as solar thermal utilization systems, wearable devices, and energy-saving buildings. However, PCM usually spontaneously crystallizes during the cooling process to release latent heat. This feature makes it difficult to achieve long-term storage of thermal energy and timely release on demand.

[0003] Long-term TES is generally based on supercooled PCM, which absorbs heat when melting. When cooling, the liquid PCM undergoes a stable supercooling process and finally vitrifies to a kinetically stable glass state. When reheated below the melting temperature, the good glass state usually first changes from the glass state to a supercooled liquid, and then to a crystalline state when the stored heat is released. This phenomenon of crystallization that occurs below the melting temperature of the material during heating is called cold crystallization. The use of supercooled PCM can avoid crystallization in the supercooled state, and store the latent heat of melting for a long time as needed. The stored heat can be released by reheating or adding seed crystals, thereby achieving long-term storage and on-demand release of thermal energy. Polyol PCMs all have a large degree of supercooling and a melting temperature mainly between 90°C and 200°C. They also have the advantages of high volumetric energy density, wide sources, and non-toxicity.

[0004] Many studies have been conducted to improve the long-term storage performance of materials by compounding polyols with polymers. Patent CN110114436A discloses a cold crystallization material and a method for utilizing cold crystallization in heat storage. The method compounds sodium polyacrylate with erythritol to prepare a cold crystallization material. Through the ion-dipole interaction between the polymer and the polar groups of PCM, the interaction between PCM molecules is interfered with and the viscosity of the material is increased, thereby extending the storage time of the material. However, the preparation conditions of this method are complicated. Summary of the invention

[0005] The embodiments of the present application provide a long-term energy storage phase change material and a preparation method thereof to solve the problem of complex preparation conditions in related technologies.

[0006] In a first aspect, the present application provides a long-term energy storage phase change material and a preparation method thereof, comprising the following steps:

[0007] Step S101, adding polyol into sodium carbonate solution, stirring and dissolving, to obtain a first mixed solution;

[0008] Step S102, adding water to calcium chloride and polyacrylic acid to mix to obtain a second mixed solution; wherein the molar ratio of sodium carbonate, calcium chloride and polyacrylic acid is 1:1:1;

[0009] Step S103, slowly adding the second mixed solution into the first mixed solution, vigorously stirring, washing, and drying to obtain a polyol hydrogel composite PCM;

[0010] Step S104, putting the obtained polyol hydrogel composite PCM into a sealed reagent bottle to observe the crystallization condition.

[0011] In some embodiments, the polyol is erythritol or a mixture of erythritol and mannitol, tretol, or sorbitol.

[0012] In some embodiments, the concentration of sodium carbonate in the sodium carbonate solution is 0.1-0.12 mol / L.

[0013] In some embodiments, the concentration of calcium chloride in the calcium chloride solution is 0.1-0.12 mol / L.

[0014] In some embodiments, the molecular weight of the polyacrylic acid is 100,000 to 450,000 g / mol.

[0015] In some embodiments, the concentration of polyacrylic acid in the polyacrylic acid solution is 0.1-0.12 mol / L.

[0016] In some embodiments, the polyol accounts for 5-17% of the total mass of the raw materials.

[0017] In some embodiments, in step S101, the stirring speed is 600-800 r / min.

[0018] In a second aspect, the present application also provides a shape-stable composite PCM prepared using the above preparation method.

[0019] On the third aspect, the present application also provides the application of the shape-stable composite PCM prepared by the above-mentioned preparation method, which can be applied to intrinsically flexible phase change films, wearable thermal management phase change nonwovens, synchronous visual / infrared stealth self-healing phase change films, etc.

[0020] When the present application uses polyacrylic acid and calcium carbonate hydrogel and polyol to prepare composite PCM:

[0021] A mixed solution of polyacrylic acid and calcium chloride is added to a solution of polyol and sodium carbonate. Sodium carbonate and calcium chloride react to form calcium carbonate. The polyacrylic acid molecular chain is cross-linked with calcium carbonate to form a network structure, and the polyol molecules are free in the network structure. The hydrogen bonds formed between the polyacrylic acid-calcium carbonate hydrogel and the polyol can increase the crystallization energy barrier and stabilize the supercooling state of the polyol. This is because the polyol, such as erythritol, has a large supercooling degree. The increase in the number of hydrogen bonds further increases the supercooling degree of the polyol, thereby achieving the cold crystallization phenomenon of no crystallization during the cooling process and crystallization during the reheating process. In addition, the moisture in the hydrogel structure is also conducive to the stable supercooling state of PCM. Even if it is cooled to 0°C, it will not crystallize. The heat can be kept in the polyol all the time, and the heat can be released by reheating when there is a heat demand, so that the polyol hydrogel composite PCM can achieve long-term energy storage characteristics and controllable heat release.

[0022] The beneficial effects of the technical solution provided by this application include:

[0023] 1. The composite PCM provided in this application can be kept at room temperature for 2 months without crystallization, and has long-term energy storage characteristics;

[0024] 2. The composite PCM prepared in this application can release heat according to demand, achieving controllable release of heat;

[0025] 3. The preparation method of the present application has simple process, short reaction time, no need for post-treatment, low production cost, and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 This is a diagram of the heat storage and heat release performance of the long-term energy storage phase change material prepared in Example 5. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0029] The embodiments of the present application provide a long-term energy storage phase change material and a preparation method thereof, which can solve the problem of complex PCM preparation conditions in the prior art.

[0030] Embodiment 1:

[0031] Example 1 provides a method for preparing a composite PCM, comprising the following steps:

[0032] (1) Weighing 60 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring it at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0033] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0034] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0035] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 1 and place it in a sealed reagent bottle to observe its crystallization.

[0036] The long-term energy storage phase change material prepared in Example 1 can be stored at room temperature for 2 months without crystallization.

[0037] Comparative Example 1:

[0038] (1) Weighing 60 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring it at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0039] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight 2000) and mixing them to obtain a second mixed solution;

[0040] (3) The second mixed solution was slowly injected into the first mixed solution at a rate of 4 mL / min and vigorously stirred at a speed of 800 r / min. The hydrogel had a flocculent structure and did not form a complete structure.

[0041] Embodiment 2:

[0042] (1) Weigh 48 g of erythritol and 12 g of mannitol and mix them, because the mass ratio of the eutectic point of erythritol and mannitol is 4:1; add them into 100 mL of 0.1 M sodium carbonate solution and stir them at a speed of 600 r / min to fully dissolve the erythritol, thereby obtaining a first mixed solution;

[0043] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0044] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0045] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 2 and place it in a sealed reagent bottle to observe its crystallization.

[0046] The long-term energy storage phase change material prepared in Example 2 can be stored at room temperature for 2 months without crystallization.

[0047] Embodiment 3:

[0048] Example 3 provides a method for preparing a composite PCM, comprising the following steps:

[0049] (1) Weighing 70 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0050] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0051] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0052] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 3 and place it in a sealed reagent bottle to observe its crystallization.

[0053] The long-term energy storage phase change material prepared in Example 3 can be stored at room temperature for 2 months without crystallization.

[0054] Embodiment 4:

[0055] Example 4 provides a method for preparing a composite PCM, comprising the following steps:

[0056] (1) Weighing 80 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0057] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0058] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0059] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 4 and place it in a sealed reagent bottle to observe its crystallization.

[0060] The long-term energy storage phase change material prepared in Example 4 can be stored at room temperature for 2 months without crystallization.

[0061] Embodiment 5:

[0062] Example 5 provides a method for preparing a composite PCM, comprising the following steps:

[0063] (1) Weighing 90 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0064] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0065] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0066] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 5 and place it in a sealed reagent bottle to observe its crystallization.

[0067] The long-term energy storage phase change material prepared in Example 5 can be stored at room temperature for 2 months without crystallization.

[0068] Embodiment 6:

[0069] Example 6 provides a method for preparing a composite PCM, comprising the following steps:

[0070] (1) Weighing 100 g of erythritol, adding it into 100 mL of 0.1 M sodium carbonate solution, stirring it at a speed of 600 r / min to fully dissolve the erythritol, and obtaining a first mixed solution;

[0071] (2) preparing 100 mL of 0.1 M calcium chloride and 0.1 M polyacrylic acid (molecular weight of 100,000) and mixing them to obtain a second mixed solution;

[0072] (3) slowly injecting the second mixed solution into the first mixed solution at a rate of 4 mL / min and vigorously stirring at a speed of 800 r / min to obtain a white erythritol mineral hydrogel composite PCM, and washing the obtained erythritol mineral hydrogel composite PCM with clean water for multiple times;

[0073] (4) Take out 20-50 g of the long-term energy storage phase change material prepared in Example 5 and place it in a sealed reagent bottle to observe its crystallization.

[0074] The long-term energy storage phase change material prepared in Example 6 can be stored at room temperature for 2 months without crystallization.

[0075] Performance test: The composite PCM of Example 1 to Example 6 was tested for heat storage and heat release performance. The results are shown in Table 1. The heat storage and heat release performance tests were performed using a differential scanning calorimeter.

[0076] Table 1: Test results of heat storage and heat release performance of phase change materials of Examples 1 to 6

[0077]

[0078] As can be seen from Table 1, the composite PCM obtained in Example 6 has the best heat storage and heat release performance, which proves that the method of using polyacrylic acid and calcium carbonate hydrogel composite polyol can effectively ensure the long-term energy storage characteristics of the material.

[0079] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0080] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0081] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a long-term energy storage phase change material, characterized in that: The following steps are involved: S101, adding a polyol into a sodium carbonate solution, stirring and dissolving, to obtain a first mixed solution; S102, adding water to calcium chloride and polyacrylic acid to mix to obtain a second mixed solution; S103, slowly adding the second mixed solution into the first mixed solution, vigorously stirring and washing, to obtain a polyol hydrogel composite PCM.

2. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The polyol is erythritol or a mixture of erythritol, mannitol, sorbitol and soda ash.

3. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The concentration of sodium carbonate in the sodium carbonate aqueous solution is 0.1-0.12 mol / L.

4. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The molar concentration of calcium chloride in the calcium chloride aqueous solution is 0.1-0.12 mol / L.

5. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The molecular weight of the polyacrylic acid is 100,000 to 450,000 g / mol.

6. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The molar concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 0.1-0.12 mol / L.

7. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The polyol accounts for 5 to 17% of the total mass of the raw materials.

8. The method for preparing a long-term energy storage phase change material according to claim 1, characterized in that: The molar ratio of sodium carbonate, calcium chloride and polyacrylic acid is 1:1:

1.

9. A long-term energy storage phase change material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Cold-crystallizing material and method for utilizing cold-crystallization in heat storing

    CN110114436A